1989
DOI: 10.1080/02699938908412711
|View full text |Cite
|
Sign up to set email alerts
|

Talking with Feeling: Integrating Affective and Linguistic Expression in Early Language Development

Abstract: The purpose of the longitudinal study reported here was to determine the developmental relation between the two systems of expression available to the young child in the period of early language learning: affect and speech. Two achievements in language were identified for a group of 12 infants: First Words, at the beginning of the single-word period (mean age about 13 months), and a Vocabulary Spurt toward the end of the period (mean age about 19 months). Affect expression was coded continuously in the stream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 53 publications
5
57
0
2
Order By: Relevance
“…Recall that internal state language ability was assessed via maternal self-report. Although researchers investigating internal state language in toddlerhood often rely on maternal reports (Bloom & Beckwith, 1989), the association between maternal reports of sympathy and internal state language in the present research could be due to the fact that mothers reported on both internal state language ability and sympathy. Consequently, clarifying our findings requires observational measures for both variables and could involve sequential analyses of more in-depth and long-term observations of children's internal state language and empathy-related reactions.…”
Section: Discussionmentioning
confidence: 73%
“…Recall that internal state language ability was assessed via maternal self-report. Although researchers investigating internal state language in toddlerhood often rely on maternal reports (Bloom & Beckwith, 1989), the association between maternal reports of sympathy and internal state language in the present research could be due to the fact that mothers reported on both internal state language ability and sympathy. Consequently, clarifying our findings requires observational measures for both variables and could involve sequential analyses of more in-depth and long-term observations of children's internal state language and empathy-related reactions.…”
Section: Discussionmentioning
confidence: 73%
“…At a very early age, infants explore their world through sensorimotor interactions that necessarily involve affective interchanges (Anooshian & Siegel, 1985;Escalona, 1981;Neisser, 1963). Bloom and her colleagues (Bloom & Beckwith, 1989;Bloom & Capatides, 1987) documented the close relationship in infancy between the expression of affect and language development and postulated further integration of affect and language as children learn to express emotion in different contexts. More generally, prior experience establishes the ways in which new events of a similar type are processed.…”
Section: Consider the Following Scenariomentioning
confidence: 99%
“…Emotional words seem to hold a special significance in the mental lexicon because both the language system and the emotional regulation system develop together during childhood. This means that words that are learned early are more tightly connected to the brain's emotional system [2]. This also indicates that words carry both a semantic meaning and an emotional meaning via amygdala mediated learning.…”
Section: Introductionmentioning
confidence: 72%